BUSINESS CRIMES IN THE FIELD OF TAXATION - Harahap, Siti Holija (Proceeding International Seminar of Islamic Studies, 2023)
Tax is a source of state revenue that has a significant contribution so that the source of tax revenue becomes a mainstay for national development. Taxes can be one of the instruments for the government to measure how much public awareness is to pay taxes or fund state administration and measure the value of people's real income and welfare. Criminal law in an effort to tackle crime in the field of taxation is to create coherence in the applied criminal law policies whose impact will not make it difficult for law enforcement officials to apply them in tax legislation. The imperative elements contained in the tax law, want to set forth a principle that the use of criminal sanctions should still pay attention to the principle of subsidiarity. In a sense, a new type of punishment that is more severe is used if other types of criminal sanctions that are lighter are deemed inappropriate or unable to support the achievement of the objective of punishment.